HTLV-1 Tax plugs and freezes UPF1 helicase leading to nonsense-mediated mRNA decay inhibition - Francesca Fiorini (Nature Portfolio, 2018)
UPF1 is a central protein in nonsense-mediated mRNA decay (NMD), but contribution of its RNA processivity to NMD is unclear. Here, the authors show how the retroviral Tax protein interacts with and inhibits UPF1, and demonstrate that UPF1’s translocase activity contributes to NMD.